China's military procurement in the reform era the setting of new directions - Evron, Yoram (Routledge contemporary China series ;, 2016)
This book explores the politics of military procurement in China under the successive leaderships of Deng Xiaoping, Jiang Zemin and Hu Jintao. It shows how China's political and military leaders have sought to adjust military procurement policy to meet China's strategic objectives, to relate it to non-military needs, to strike a balance between the import of weapons and indigenous production, and to determine the connections between hardware and other components of military power.